Influenza vaccination hesitancy and related factors among pregnant and breastfeeding women: A cross-sectional study - Dania Comparcini; Giancarlo Cicolini; Melania Totaro; Letizia Governatori; Francesco Pastore; Daniela Miniscalco; Maria Elena Flacco; Eustachio Cuscianna; Silvio Tafuri; Valentina Simonetti (Human Vaccines & Immunotherapeutics)
Achieving safe influenza vaccination coverage among pregnant and breastfeeding women is a global health goal due to the potential risks of serious influenza for both mother and child. However, vaccine hesitancy remains a significant barrier to vaccination uptake. Since anxiety represents a determinant in vaccine decision-making, this study aimed to assess influenza vaccination hesitancy and anxiety levels in this population and to explore the association between women’s characteristics, their reluctance, and anxiety levels. A multicentre, cross-sectional study was conducted between February and June 2022 using structured phone interviews to assess: (1) socio-demographics and clinical history; (2) anti-flu vaccination status, previous anti-flu vaccination, and Sars-CoV-2 infection history; (3) insights into influenza vaccination during pregnancy; (4) attitudes toward anti-flu vaccination, using the Vaccination Attitudes Examination (VAX) Scale; (5) anxiety levels, measured by the Self-Rating Anxiety Scale (SAS). Among the 387 participants, 22.8% were already vaccinated or expressed willingness to be vaccinated against influenza, and 54% had an anxiety disorder. While anxiety was not significantly associated with vaccine hesitancy, ongoing pregnancy emerged as an independent predictor of anxiety. Higher educational levels, ongoing pregnancy, already being vaccinated or willingness to get vaccinated, and being employed were associated with reduced vaccine hesitancy, while prior SARS-CoV-2 infection with increased hesitancy. Fear of unpredictable events and lack of healthcare professionals’ recommendations emerged as reasons for vaccine reluctance. Given the low coverage rates, these findings highlight the need for health services to enhance vaccination efforts and provide clear recommendations to counter misinformation and ensure accurate vaccine safety information.